Measurement of social recognition in the perception of a person who has experienced a traumatic event. Polish adaptation of the Social Recognition Questionnaire (SAQ) - Szumiał, Szymon; Lis-Turlejska, Maja; Rzeszutek, Marcin; Drapała, Iwona (Przegląd Psychologiczny, 2021)
OBJECTIVE. The aim of the study was to adapt the Social Acknowledgment Questionnaire (SAQ) for the Polish-speaking population. The questionnaire is used to assess the socio-interpersonal responses to people who have experienced traumatic events. METHOD. Studies were carried out in five groups representing different populations. The reliability of the SAQ was estimated using Cronbach’s alpha coefficients and intra-class correlation coefficients. The accuracy of the SAQ was checked with the use of confirmatory factor analysis and an analysis of the correlations between SAQ results vs. the severity of post-traumatic stress disorder (PTSD) symptoms and depression symptoms. RESULTS. The Polish adaptation of the SAQ meets the criteria of reliability and validity. The values of reliability were found to be sufficiently high, taking into account the dimensions of internal cohesion expressed by the values of Cronbach’s alpha coefficients, as well as stability expressed by intra-class correlation coefficients. The SAQ factor structure requires further analyses involving larger samples. CONCLUSIONS. Social recognition can be a dynamic variable influenced by therapeutic interventions. The Polish version of the SAQ is a tool with good psychometric properties, which can be helpful in assessing the risk of PTSD development. It can also be a valuable questionnaire for further research in the context of prevention and treatment strategies for people with PTSD and their relatives.